2006
DOI: 10.1074/jbc.m603096200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements for Heparin/Heparan Sulfate Binding to Type V Collagen

Abstract: Collagen-proteoglycan interactions participate in the regand native collagen V molecules formed much more stable complexes with heparin than HepV, and collagen V bound to heparin/heparan sulfate with a higher affinity (in the nanomolar range) than HepV. Heat and chemical denaturation strongly decreased the binding, indicating that the triple helix plays a major role in stabilizing the interaction with heparin. Collagen V and HepV may play different roles in cell-matrix interactions and in matrix assembly or re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…2A) or collagen V binding (Supplementary Fig. 2B), demonstrating that the heparan sulfate sequences that bind these ligands (Guimond et al, 1993; Ricard-Blum et al, 2006) are resistant to modification by these oxidants. As well as maintaining their ability to bind FGF-2, the heparan sulfate chains of HOCl/HOBr-modified perlecan (oxidant/perlecan molar ratios of 100 and 1000) maintained their ability to stimulate proliferation of FGFR1c expressing cells in response to FGF-2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 94%
“…2A) or collagen V binding (Supplementary Fig. 2B), demonstrating that the heparan sulfate sequences that bind these ligands (Guimond et al, 1993; Ricard-Blum et al, 2006) are resistant to modification by these oxidants. As well as maintaining their ability to bind FGF-2, the heparan sulfate chains of HOCl/HOBr-modified perlecan (oxidant/perlecan molar ratios of 100 and 1000) maintained their ability to stimulate proliferation of FGFR1c expressing cells in response to FGF-2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Covalently immobilized VEGF surfaces were generated using the same general approach except that heparin was modified with an amine reactive photoactivatable group that could be activated post VEGF immobilization (Figure 1B). Heparin was chosen because it has been previously shown to bind with VEGF through its heparin binding domain located at the C-terminus of the protein (4) and because it can also bind ECM proteins such as fibronectin (32, 33), collagen (34), vitronectin (35), and laminin (36). The binding of ECM proteins is essential to the study of VEGF/VEGFR-2 signaling cascades since the binding of cells through different integrin receptors as well as the binding of VEGF with the ECM molecules can modulate the signaling responses induced (33, 37).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous observations in cho mice (Li et al, 1995), less proteoglycan aggregates were observed in the cartilage matrix of col11a1-morphants. Collagen XI α1 chain contains three different heparin binding sites that can bind heparan sulfate proteoglycans (Delacoux et al, 2000;Vaughan-Thomas et al, 2001;Blum et al, 2006). It is thus conceivable that the lack of collagen XI α1 alters retention of proteoglycans in cartilage tissues and, consequently affects interactions with other matrix components.…”
Section: Collagen XI α1 Knockdown Affects Zebrafish Extracellular Matmentioning
confidence: 97%